2007
DOI: 10.1172/jci31446
|View full text |Cite
|
Sign up to set email alerts
|

Principles of adoptive T cell cancer therapy

Abstract: The transfusion of T cells, also called adoptive T cell therapy, is an effective treatment for viral infections and has induced regression of cancer in early-stage clinical trials. However, recent advances in cellular immunology and tumor biology are guiding new approaches to adoptive T cell therapy. For example, use of engineered T cells is being tested as a strategy to improve the functions of effector and memory T cells, and manipulation of the host to overcome immunotoxic effects in the tumor microenvironm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
168
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(169 citation statements)
references
References 132 publications
1
168
0
Order By: Relevance
“…2 Early clinical studies have demonstrated a 50-70% clinical response in patients. [3][4][5] However, the optimal protocols for expansion of T cells, especially antigenspecific CD8 C T cells, remain to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…2 Early clinical studies have demonstrated a 50-70% clinical response in patients. [3][4][5] However, the optimal protocols for expansion of T cells, especially antigenspecific CD8 C T cells, remain to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Adoptive transfer of antigen-specific CD8 T cells into hosts represents a promising approach to treat tumors and viral infections [1][2][3][4]. To generate sufficient numbers of T cells for this therapy, T cells have to be stimulated and expanded in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Adoptive immunotherapy with T cells can effectively treat patients with EBV-associated malignancies and metastatic melanoma, and application of this treatment is broadening as our ability to generate T cells targeting diverse tumor antigens improves (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Our expanding capacity to target novel antigens is driven, in part, by advances in genetic engineering that permit high efficiency transfer of genes encoding tumor specific T-cell receptors (TCR) into open repertoire mature T cells.…”
mentioning
confidence: 99%